Concepts and requirements for the structural-functional model of the professional trainings system of future geography teachers - Chubrei, Olexandra (Journal of Education, Health and Sport, 2019)
The article describes the essence of the concept and defines the requirements for the author's model of future geography teachers preparation for professional activity on the basis of competence approach, which will ensure its validity and effectiveness. In psychological and pedagogical studies, the concept of "modeling" is seen as the highest special form of clarity, means of presenting information that provides a deeper disclosure of the essence of the phenomenon, which is being analyzed. The author found, that model is to be the means by which was obtained new knowledge about the object of study. It allows to come up with a perfect diagram of a real object by defining its structural components and their relationships. By developing the model, the following requirements should be observed: adequacy, openness, systematic, stability, optimality, prognosticity, rationality, diagnostics and taking into account the stabilizing factors, which ensured the construction of an effective author's structural and functional model of the phenomenon under study.